Costs and health-related quality of life in Alpha-1-Antitrypsin Deficient COPD patients - Florian M. Karl; Rolf Holle; Robert Bals; Timm Greulich; Rudolf A. Jörres; Annika Karch; Armin Koch; Stefan Karrasch; Reiner Leidl; Holger Schulz; Claus Vogelmeier; Margarethe E. Wacker; et al. (Respiratory Research, 2017)
Abstract Background Alpha-1-Antitrypsin Deficiency (AATD) is an economically unexplored genetic disease. Methods Direct and indirect costs (based on self-reported information on healthcare utilization) and health-related quality of life (HRQL, as assessed by SGRQ, CAT, and EQ-5D-3 L) were compared between 131 AATD patients (106 with, 25 without augmentation therapy (AT)) and 2,049 COPD patients without AATD participating in the COSYCONET COPD cohort. The medication costs of AT were excluded from all analyses to reveal differences associated with morbidity profiles. The association of AATD (with/without AT) with costs or HRQL was examined using generalized linear regression modelling (GLM) adjusting for age, sex, GOLD grade, BMI, smoking status, education and comorbidities. Results Adjusted mean direct annual costs were €6,099 in AATD patients without AT, €7,117 in AATD patients with AT (excluding costs for AT), and €7,460 in COPD patients without AATD. AATD with AT was significantly associated with higher outpatient (+273%) but lower inpatient (−35%) and medication costs (−10%, disregarding AT) compared with COPD patients without AATD. There were no significant differences between groups regarding indirect costs and HRQL. Conclusion Apart from AT costs, AATD patients tended to have lower, though not significant, overall costs and similar HRQL compared to COPD patients without AATD. AT was not associated with lower costs or higher HRQL. Trial registration NCT01245933